Analisa perilaku herding pada saham ipo emisi jumbo di bursa efek indonesia tahun 2021-2023 - Zulhelfi, Zulhelfi (Departement Of Accounting, Indonesian Cooperative Institute, Indonesia, 2023)
This research was conducted to observe herding behavior during the initial public offering (IPO) of stocks on the Indonesia Stock Exchange from 2021 to 2023. The listing and trading of stocks for the first time generally generate high interest among investors to participate in transactions, reflected in the high volume and frequency of trades in the initial trading days, along with significant stock price movements. The method employed in this study is employing Cross-Sectional Absolute Deviation (CSAD) to determine the dispersion of IPO stock returns. This dispersion is then analyzed concerning market returns through multiple linear regression analysis. To ensure the research reflects market transparency, avoiding elements of market manipulation and short-term speculation, only stocks with large issuance values (above Rp 500 billion) were included in the study, observing only the first three days of trading. The research findings indicate the absence of herding behavior among stocks with large issuances on the Indonesia Stock Exchange. This suggests that investors in the Indonesia Stock Exchange, during the observation period, made rational investment decisions and did not exhibit herding behavior, indicating that investors in the Indonesian capital market demonstrate rational behavior similar to other developed countries.